PENGARUH ATTITUDE TOWARDS ENTREPRENEURSHIP, SUBJECTIVE NORMS, DAN PERCEIVED BEHAVIOURAL CONTROL TERHADAP INTENSI BERWIRAUSAHA - Ayi Syabani; Dwi Retno Utari; Fazar Nuriansyah (FKIP Unswagati, 2024)
This research is motivated by Indonesia's low Global Entrepreneurship Index, which ranked 90th out of 137 countries worldwide in 2018. The study aims to investigate the influence of Attitude Towards Entrepreneurship, Subjective Norms, and Perceived Behavioral Control on entrepreneurial intention. The research employs a survey research method, with the population and sample being students of the Economics Education program at the Faculty of Economics and Business Education, Indonesia University of Education. The data analysis technique utilized is multiple linear regression. The findings of this research indicate that: (1) Attitude Toward Entrepreneurship and Subjective Norms positively influence Entrepreneurial Intention; (2) Perceived Behavioral Control does not affect Entrepreneurial Intention; (3) Attitude Towards Entrepreneurship, Subjective Norms, and Perceived Behavioral Control collectively have a positive impact on Entrepreneurial Intention.